In vitro analysis of nanoparticles released from polyamide nanomaterial composites during drilling process - Irfan, Adeel; Sachse, Sophia; Njuguna, James A. K.; Zhu, Huijun (Cranfield University, 2011)
Nanomaterials provide a new avenue of progress into technological development. By manipulating materials on the very basic atomic and molecular levels the property of a given material can be specifically altered to suit the purpose of intended applications. However, nanomaterials (nanoparticles and nanolayers) have a more complex nature in physiochemical properties and surface reactivity than their larger counterparts. Therefore, the release of these nanomaterials as dust during crushing or drilling may lead to serious health hazards for humans and the surrounding environment. This study, supported by the NEPHH (Nanomaterial-related Environmental Pollution Health Hazards), addresses two important questions about nanomaterials: - Whether nanomaterials can be released from physical process of nanoproducts. - Toxicity potential of nanodusts generated from nanoproducts in comparison with reference products. Both questions address a massive gap in knowledge for toxicity and more specifically nanomaterial toxicity.